Peranan Kepolisian Dalam Memberantas Tindak Pidana Pencurian Dengan Kekerasan Di Wilayah Patumbak (Studi Kasus Di Polsek Patumbak) - Fransisco Lumban Batu; Taufik Siregar; Muazzul Muazzul (Universitas Medan Area, 2020)
Violent theft is one of the diseases of society which merges with crime, which in the historical process from generation to generation turns out that the crime is a crime that harms and tortures others. This type of research is normative juridical that is by means of library research. The results of this study are the role of the Patumbak police in violent theft as stipulated in Article 365 of the Criminal Code, in accordance with the duties and authorities of the police, conducting investigations and investigations as well as arresting the perpetrators and processing in accordance with applicable legal provisions, the factors causing the crime of theft with violence in the Patumbak Sector Police Sector are due to economic factors, social factors and illegal drugs, education factors and also the lack of guidance. Obstacles in efforts to deal with violent theft due to the lack of police personnel in the field in the Patumbak Sector Police area, the ability of the police to handle cases is still lacking, the lack of tools needed by members of the National Police in handling cases and the vast area of the Patumbak Sector Police.